Automated Extraction of Geographic Locations from Natural Language Text: Implications for Process Control and Mechanism - Ashutosh Das; B. Sahithi; Pallavi Choudhury; Neelamadhab Padhy (Proceedings)
Context: Natural Language Processing (NLP) techniques, along with database management tools and fuzzy string-matching libraries, play a pivotal role in automating the extraction of geographic locations from textual data [...]